Herbal Substances with Antiviral Effects: Features and Prospects for the Treatment of Viral Diseases with Emphasis on Pro-Inflammatory Cytokines - Bjørklund, Geir; Lysiuk, Roman; Semenova, Yuliya; Lenchyk, Larysa; Dub, Natalia; DoŦ#159;a, Monica D.; Hangan, Tony (Current Medicinal Chemistry, 2024)
Viral diseases have a significant impact on human health, and three novel coronaviruses (CoV) have emerged during the 21st century. In this review, we have emphasized the potential of herbal substances with antiviral effects. Our investigation focused on the features and prospects of viral disease treatment, with a particular emphasis on proinflammatory cytokines. We conducted comprehensive searches of various databases, including Science Direct, CABI Direct, Web of Science, PubMed, and Scopus. Cytokine storm mechanisms play a crucial role in inducing a pro-inflammatory response by triggering the expression of cytokines and chemokines. This response leads to the recruitment of leukocytes and promotes antiviral effects, forming the first line of defense against viruses. Numerous studies have investigated the use of herbal medicine candidates as immunomodulators or antivirals. However, cytokine-storm-targeted therapy is recommended for patients with acute respiratory distress syndrome caused by SARS-CoV to survive severe pulmonary failure. Our reviews have demonstrated that herbal formulations could serve as alternative medicines and significantly reduce complicated viral infections. Furthermore, they hold promising potential as specific antiviral agents in experimental animal models.
Keywords: SARS-CoV-2